2012
DOI: 10.4172/1747-0862.1000054
|View full text |Cite
|
Sign up to set email alerts
|

The use of equine influenza pseudotypes for serological screening

Abstract: Standard assays used for influenza serology present certain practical issues, such as inter-laboratory variability, complex protocols and the necessity for handling certain virus strains in high biological containment facilities. In an attempt to address this, avian and human influenza HA pseudotyped retroviruses have been successfully employed in antibody neutralization assays. In this study we generated an equine influenza pseudotyped lentivirus for serological screening. This was achieved by co-transfection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 26 publications
2
28
0
Order By: Relevance
“…Thus far, it is thought that the assay demonstrates increased sensitivity as some serum samples were defined as negative by SRH but positive by PVNA. Overall 65% correlation was shown between the two assays (Scott et al, 2012).…”
Section: (B) Assay Applications: Advantages and Disadvantagesmentioning
confidence: 83%
“…Thus far, it is thought that the assay demonstrates increased sensitivity as some serum samples were defined as negative by SRH but positive by PVNA. Overall 65% correlation was shown between the two assays (Scott et al, 2012).…”
Section: (B) Assay Applications: Advantages and Disadvantagesmentioning
confidence: 83%
“…The use of pseudotypes as alternatives to wild-type influenza viruses, including HPAI strains and pandemic strains, has been implemented in neutralization assays, also referred to as pseudotype-based neutralization (pp-NT) assays. Previous studies have reported that results from HI, MN and SRH assays correlate well with those obtained by pp-NT assay [128,[137][138][139]. For the pp-NT assay, twofold serial dilutions of sera are incubated with a predetermined amount (quantification is done via the measurement of reporter gene expression) of pseudotypes and incubated for 1 h at 37°C in a 96-well plate.…”
Section: • • New Assays Pseudotype Virus Neutralization Assaymentioning
confidence: 85%
“…Higher titres of the Richmond/07 PV were obtained using HAT than with TMPRSS2 while titres obtained with Newmarket/79 were equivalent using HAT or TMPRSS2. The use of TMPRSS2 to successfully generate PVs expressing HA from various subtypes has been previously reported [13,14], and TMPRSS2 was used to generate the first reported equine influenza PV [5]. The HAT protease has also been used previously to generate PVs expressing human H3, H1, and H5 [14].…”
Section: Discussionmentioning
confidence: 99%
“…The full-length HA genes of A/equine/Newmarket/1979 (H3N8) and A/equine/Richmond/2007 (H3N8) were kindly provided by Dr. Adam Rash and Dr. Debra Elton (Animal Health Trust, Newmarket, UK) who PCR-amplified the HA gene using the custom primers (Invitrogen) described in [5]. The PCR fragments were digested with restriction enzymes EcoRV/BamHI and BamHI/XhoI (Thermo Scientific) for A/equine/Newmarket/1979 and A/equine/Richmond/2007, respectively, and cloned into the pI.18 expression plasmid.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation